Relative Efficacy of Liquid Nitrogen Fertilizers in Dryland Spring Wheat - Olga S. Walsh; Robin J. Christiaens (International Journal of Agronomy)
The study was conducted in 2012 and 2013 at three locations in North Central and Western Montana (total of 6 site-years) to evaluate the relative efficacy of three liquid nitrogen (N) fertilizer sources, urea ammonium nitrate (UAN, 32-0-0), liquid urea (LU, 21-0-0), and High NRGN (HNRGN, 27-0-0-1S), in spring wheat (Triticum aestivum L.). In addition to at-seeding urea application at 90 kg N ha−1 to all treatments (except for the unfertilized check plot), the liquid fertilizers were applied utilizing an all-terrain vehicle- (ATV-) mounted stream-bar equipped sprayer at a rate of 45 kg N ha−1 at Feekes 5 growth stage (early tillering). Three dilution ratios of fertilizer to water were accessed: 100/0 (undiluted), 66/33, and 33/66. The effects of N source and the dilution ratio (fertilizer/water) on N uptake (NUp), N use efficiency (NUE), spring wheat grain yield (GY), grain protein (GP) content, and protein yield (PY) were assessed. The dilution ratios had no effect on GY, GP, PY, NUp, and NUE at any of the site-years in this study. Taking into account agronomic and economic factors, LU can be recommended as the most suitable liquid N fertilizer source for spring wheat cropping systems of the Northern Great Plains.